INAKTIVASI MIKROBA Staphylococcus aureus DALAM SUSU MENGGUNAKAN MEDAN LISTRIK BERDENYUT TEGANGAN TINGGI - Nurismanto, Rudi; HP, Sudaryati; Rahmita, Ruhi Dian (REKAPANGAN, 2011)
Pulsed  electric  field  processing  represents  a  promising  non-thermal  technology which involves the application of pulses of high voltage (20-80 kV/cm) for less than one second  to  fluid  foods  placed  between  two  electrodes.  During  the  application  of  certain PEF conditions microbial inactivation occurs by causing a pore formation and destruction of  the  cell  membranes The  purposes  of  the  present  study  were  (i)  to  inactivated  of Staphylococcus  aureudecreas  using  pulsed  electric  field  and  (ii)  physicochemical properties of raw milk. Intensity field strength that used are  30 and 60 kV/cm, with pulses number  10,  20, and 30. The  results  showed  that  higher  decrease  of  population  of Staphylococcus  aureus  with intensity 60  kV/cm and pulses  number  30 (0,6  log cycle) and PEF methods give unsignificant effect on pH and total acid.Key words : pulsed electric field, population,  Staphylococcus aureus